DEVELOPING WEB-BASED PERFORMANCE ASSESSMENT IN INTEGRATED SCIENCE COURSE - Wahyuni, S. (Jurnal Pendidikan IPA Indonesia, 2015)
This research aims to develop a web-based performance assessment in Integrated Science course. The research was Research and Development (R & D). The expert validation of developed products resulted the average percentage of 3.88 for content category, 3.94 for format category, and 3.78 for language category. Meanwhile, critical thinking skill aspect resulted percentage of 92.20 basic clarification indicators, 90.05 for basic for the decision category, and 94.67 for inference category. Students also responded positively to web-based performance assessment in Integrated Science course.